Dyadic effect of Gottman’s psycho-educational intervention and mediated effect of adult attachment style on marital communication among Iranian couples in Shiraz, Iran - Deylami, Neda (2016)
The accumulated evidence on marital quality indicates that marital communication patterns (MCP) and its training is necessary to reduce emotionally and economically cost of marital problems. However, despite the high effectiveness of Gottman’s intervention as one of the most effective family education, the interpersonal and intrapersonal factors that may influence on it, were not included in the previous studies. Indeed, dyadic interaction between couples as an interpersonal factor and the effect of the spouse’s characteristics on their partner such as adult attachment style (AAS) as an intrapersonal factor on MCP have been ignored. The aims of study were examined the effect of Gottman’s Psychoeducational Intervention (GPI) on MCP and also the simultaneous dyadic evaluation of Acquired Skills of Gottman’s Psychoeducational Intervention (AS-GPI) on MCP as well as assessing of multiple mediating effect of AAS on the association between AS-GPI and MCP that would significantly fill these knowledge gaps. This quantitative study with two sub-researches on experimental and correlation designs attempted to provide a more comprehensive understanding of improvements in marital communication among 72 couples in Shiraz –Iran. The first sub-research was an experimental-longitudinal design with 144 spouses. The experimental group underwent eight weeks of continual sessions and a one-year follow-up. Participants’ MCP were evaluated by CPQ. The results of RM-ANOVA indicated that GPI can improve significantly participants’ constructive communication (CC) and decrease their total demand-withdraw communication (TWDC) and mutual avoidance communication (MAC) across the time. This improvement was maintained after a one-year period among the participants without any gender biased effect. The second sub-research followed the correlational design in two parts; the first, an Actor-Partner Interdependence Model (APIM) using path analyses procedure was used to evaluate the dyadic effect of AS-GPI on MCP among 36 couples. Couples were evaluated by CPQ for their MCP and SRHs for their AS-GPI. APIM analyses indicated that actor effect for CC was significant, while the partner effect was supported for men only. Actor effects in TWDC were significant for both spouses, however the partner effect was just only significant for wives. Furthermore, wives’ AS-GPI significantly decreased their own and partners’ MAC; while for husbands were not significant. In the second part the correlational design with Multiple Mediation Model using the PROCESS Macro was evaluated the multiple mediation effect of adult attachment style (AAS) on the association between AS-GPI and MCP among 72 spouses. Participants were assessed by RAAS for their AAS and also assessed by CPQ and SRHs. Through PROCESS Macro a path in which AS-GPI leaded to marital communication patterns, mediated by adult attachment style was found. The findings showed that all three sub-scales of attachment styles, including close, depend, and anxiety, significantly mediated the effect of AS-GPI on CC, while they partially mediated the MAC and did not mediate the TWDC. Marriage counselors can use these results and its theoretical and practical implications to achieve a holistic and deep understanding of the underpinnings of marital life and, ultimately, reduce the high rate of divorce in Iran and other countries. This study highly recommends for more generalization to select a more ethnically diverse population, and cross-national evaluation of another population of Iran and another countries. It is suggested to increase sample size for studying dyadic interaction with SEM and for considering of limitation in the experimental research, to be better to select two or three experimental groups instead of only one group. This study suggests to utilize APIMeM for achieving more information about dyadic mediated effect of AAS. This study encourages the interdisciplinary researches on the legal necessity for GPI among couples in dissolution situations.